2011
DOI: 10.2147/copd.s22823
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term noninvasive ventilation in hypercapnic COPD patients: a randomized controlled pilot study

Abstract: IntroductionNoninvasive ventilation (NIV) is a well-established treatment for acute-on- chronic respiratory failure in hypercapnic COPD patients. Less is known about the effects of a long-term treatment with NIV in hypercapnic COPD patients and about the factors that may predict response in terms of improved oxygenation and lowered CO2 retention.MethodsIn this study, we randomized 15 patients to a routine pharmacological treatment (n = 5, age 66 [standard deviation ± 6] years, FEV1 30.5 [±5.1] %pred, PaO2 65 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…Forced expiratory volume in 1 second was measured in two further studies; however, in one 82 no post-treatment data were presented (it was stated that there were no significant changes in either arm), and in the other 91 the data presented for SDs appeared to be incorrect. The RCT by Köhnlein et al…”
Section: Clinical Effectiveness Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forced expiratory volume in 1 second was measured in two further studies; however, in one 82 no post-treatment data were presented (it was stated that there were no significant changes in either arm), and in the other 91 the data presented for SDs appeared to be incorrect. The RCT by Köhnlein et al…”
Section: Clinical Effectiveness Review Resultsmentioning
confidence: 99%
“…Results from only one study 79,80 with a stable population were adjusted for baseline (this study had more intensive usual care in both arms). Three further studies (in a stable population) measured PaO 2 but were not included: two 74,76 found no significant difference and the other 91 appeared to have errors in the reported SD.…”
Section: Clinical Effectiveness Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The device has been successfully used to improve exercise tolerance in COPD patients by increasing respiratory muscle strength, 38 and its long term use provides a better ventilation-perfusion match, and better blood gases and lung function through a mass-flow redistribution. 39 The efficacy of BiPAP has been evaluated in acute settings as well: in acute exacerbation of COPD, its use leads to an increase of arterial oxygen partial pressure (PaO 2 ), a reduction of intubation rate, an amelioration of respiratory and other vital parameters, and a reduction in in-hospital mortality; 3,4 as regards acute cardiogenic pulmonary edema, the combination of inspiratory assistance with expiratory positive airway pressure can effectively alleviate respiratory distress, and as a consequence bilevel ventilation is considered more effective than continuous positive airway pressure (CPAP). 5,16 Systematic reviews have shown the benefit of BiPAP in the management of acute cardiogenic pulmonary edema, with reduction in the need for invasive mechanical ventilation and reduction of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Following the changes in these image-based outcome parameters provides a strong indication of the efficiency and response to therapies ( figure 3). In previous studies, this concept has been applied to long-acting b 2 -agonists (LABAs) [32], a combination of a LABA and an inhaled corticosteroid [30], a short-acting anticholinergic, a short-acting b 2 -agonist [31] and non-invasive ventilation [33]. The concept has been validated using gamma scintigraphy [34], single-photon emission computed tomography [35] and HP MRI [36].…”
Section: Functional Respiratory Imagingmentioning
confidence: 99%